Failure prediction in sheet metal forming technology : a combination between finite element simulation and plastic instability in complex strain paths - Augusto Duarte Campos Barata da Rocha (2006)
The optimization of sheet metal processes through the use of numerical simulations has become a key factor to a continuously increasing requirement for time and cost efficiency, for quality improvement and materials saving, in many manufacturing areas such as automotive, aerospace, building, packaging and electronic industries. Finite Element Simulation allows accurate predictions of stress and strain distributions in complex automotive stamped parts. However, the prediction of localized necking is a difficult task since the onset of necking is strongly dependent on the strain paths imposed to the parts. Plastic instability numerical models have been used to predict such behavior and recent and more accurate constitutive models have been applied in these calculations. This paper describes the combination of Finite Element Analysis, to describe the evolution of strain gradients in stamped parts, with a Plastic Instability Model developed to predict localized necking under complex strain paths. Several constitutive laws are used and comparisons are made with experiments in stamped parts. It is shown that considering the non linear strain paths in the analysis, more accurate failure predictions are achieved. Concerning failure the work described in this paper shows the need to include a post processor analysis of failure, capable of predicting the behavior of the material under non-linear strain paths. Taking this phenomenon into account, it is shown that it is possible to accurately predict the onset of localized necking.